2018
DOI: 10.1016/j.euo.2018.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Dose-dense Gemcitabine and Cisplatin in Muscle-Invasive Bladder Cancer: Results of a Phase 2 Trial

Abstract: Background Accelerated (also termed dose-dense, DD) chemotherapy regimens such as accelerated methotrexate, vinblastine, doxorubicin, and cisplatin have shown better efficacy and tolerability in the metastatic setting, and shortened the time to surgery in the neoadjuvant setting compared to standard-schedule regimens. We hypothesized that a DD schedule of gemcitabine and cisplatin (GC) would shorten the time to surgery and yield similar pathologic complete response rates (pT0) in patients with muscle-invasive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…Correlation between NAC related AEs and dosing are conflicting [11,17]. While Iyer et al found 6 cycles of CG to be safe, Anari et al had to close their study early due to higher than suspected rate of serious vascular events [11,20]. These were both relatively small phase II studies evaluating efficacy and safety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Correlation between NAC related AEs and dosing are conflicting [11,17]. While Iyer et al found 6 cycles of CG to be safe, Anari et al had to close their study early due to higher than suspected rate of serious vascular events [11,20]. These were both relatively small phase II studies evaluating efficacy and safety.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Iyer et al dose adjustment were necessary for 39% of patients and 67% of patients received the chemotherapy as planned [11]. In the study by Anari et al 23% of patients suffered from serious vascular event during NAC, but 94% of the patients were fit for RC showing that even after grade IV complication surgery can be performed in most cases [20]. In Finland, either three or four cycles of CG within three or four week interval is normally given.…”
Section: Discussionmentioning
confidence: 99%
“…Predictive biomarkers reported so far for CDDP sensitivity in bladder cancer have not been consistent among studies, potentially because of the reliance on small cohorts, retrospective or post-hoc analyses, the difference in chemotherapy regimens, outcome measurements and sequencing techniques, consequently producing conflicting results. 19,46,55 Several prospective clinical trials are underway that will attempt to validate the DDR genes as biomarkers. In addition, the fullyaccrued SWOG S1314 study was a randomized controlled phase II trial assigning patients with MIBC to dose-dense MVAC or gemcitabine plus CDDP in a neoadjuvant setting before cystectomy.…”
Section: Ddr Genesmentioning
confidence: 99%
“…Taken together, our findings should sensitize the urologic community to the importance of considering and providing CHT in patients with pT4a UCUB, ideally using the most modern criteria that do not rely on a specific chronologic age cutoff and do provide flexibility 23 with respect to other classic exclusion criteria, such as GFR. 24,25 Finally, to the best of our knowledge, our study represents the first report that clearly shows a survival benefit of CHT in men with UCUB with prostatic stromal invasion (pT4a) treated with radical cystectomy in a contemporary population-based cohort.…”
Section: Giuseppe Rosiello Et Almentioning
confidence: 63%